2017
DOI: 10.32607/2075-8251-2017-9-4-92-100
|View full text |Cite
|
Sign up to set email alerts
|

Direct Molecular Fishing of New Protein Partners for Human Thromboxane Synthase

Abstract: Thromboxane synthase (TBXAS1) catalyzes the isomerization reaction of prostaglandin H2 producing thromboxane A2, the autocrine and paracrine factor in many cell types. A high activity and metastability by these arachidonic acid derivatives suggests the existence of supramolecular structures that are involved in the regulation of the biosynthesis and directed translocation of thromboxane to the receptor. The objective of this study was to identify TBXAS1 protein partners from human liver tissue lysate using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The PTGIS protein was covalently immobilized on the activated CNBr-sepharose 4B via amino groups of the protein. A similar protocol has already been used to immobilize recombinant thromboxane synthase [16] and some recombinant proteins encoded by genes on Chromosome 18 [12,14,25] on this sorbent. The specificity of direct molecular fishing was analyzed by SPR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The PTGIS protein was covalently immobilized on the activated CNBr-sepharose 4B via amino groups of the protein. A similar protocol has already been used to immobilize recombinant thromboxane synthase [16] and some recombinant proteins encoded by genes on Chromosome 18 [12,14,25] on this sorbent. The specificity of direct molecular fishing was analyzed by SPR.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that the non-peptide endogenous bioregulator isatin (Mw = 147 Da) bound some cytochrome P450s isoenzymes and influenced the affinity of protein–protein interactions [16,53,54]. Therefore, to continue this investigation, SPR validation of the isatin binding (injected as analyte) with PTGIS protein immobilized on the optical chip was performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations